Cerebral blood volume estimation by ferumoxytol‐enhanced steady‐state MRI at 9.4 T reveals microvascular impact of α1‐adrenergic receptor antibodies. (24th July 2014) - Pohlmann, Andreas; Karczewski, Peter; Ku, Min‐Chi; Dieringer, Babette; Waiczies, Helmar; Wisbrun, Natali; Kox, Stefanie; Palatnik, Irina; Reimann, Henning Matthias; Eichhorn, Christina; Waiczies, Sonia; Hempel, Petra; et al.
<x xml:space="preserve">Abstract</x> Cerebrovascular abnormality is frequently accompanied by cognitive dysfunctions, such as dementia. Antibodies against the α1‐adrenoceptor (α1‐AR) can be found in patients with Alzheimer's disease with cerebrovascular disease, and have been shown to affect the larger vessels of the brain in rodents. However, the impact of α1‐AR antibodies on the cerebral vasculature remains unclear. In the present study, we established a neuroimaging method to measure the relative cerebral blood volume (rCBV) in small rodents with the ultimate goal to detect changes in blood vessel density and/or vessel size induced by α1‐AR antibodies. For this purpose, mapping of R2* and R2 was performed using MRI at 9.4 T, before and after the injection of intravascular iron oxide particles (ferumoxytol). The change in the transverse relaxation rates (ΔR2*, ΔR2) showed a significant rCBV decrease in the cerebrum, cortex and hippocampus of rats (except hippocampal ΔR2), which was more pronounced for ΔR2* than for ΔR2. Immunohistological analyses confirmed that the α1‐AR antibody induced blood vessel deficiencies. Our findings support the hypothesis that α1‐AR antibodies lead to cerebral vessel damage throughout the brain, which can be monitored by MRI‐derived rCBV, a non‐invasive neuroimaging method. This demonstrates the value of rCBV estimation by ferumoxytol‐enhanced MRI at 9.4 T, and further underlines the significance of this antibody in brain diseases involving vasculature impairments, such as dementia. Copyright © 2014 John Wiley & Sons, Ltd.